EVALUASI KOORDINAT TDT ORDE 3 HASIL UKURAN RECEIVER GNSS CORS RTK NTRIP - , ADY SATYA KURNIAWAN, Ir. Nurrohmat Widjajanti, MT., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
CORS or Continuously Operating Reference Station is a positioning technology based on GNSS (Global Navigation Satellite System). Nowadays, CORS is developed by Badan Pertanahan Nasional (BPN RI). One example of the use of CORS is for maintenance of the Cadastral Control Point third order (3 rd order TDTs). Therefore the precision of the coordinates measured using GNSS CORS RTK NTRIP receiver need to be evaluated. The project was done in Bantul regency with 30 samples of the 3 rd order TDTs. The coordinates resulted from RTK NTRIP GNSS CORS method are compared to the coordinates of the buku tugu, which has measured by Leica R 261 receiver with static relative method. The evaluation is carried out using the significance test of horizontal displacement and the tolerance computation of the displacement. The result of this study indicate that the HRMS of the RTK NTRIP method can achieve the centimeter fractions. The result of the significant test concluded that there are a significant differences between the measured coordinates and the coordinates of the buku tugu. The difference is probably caused by the earthquake that occurred in 2006 as well as due to the difference in used datums, which the coordinates of buku tugu are using WGS 1984 while the measured coordinates are using ITRF.